Optimal Control of Nonlinear Dynamic Econometric Models: An Algorithm and an Application - Viktoria Blüschke-Nikolaeva; Dmitri Blüschke; Reinhard Neck (Verein für Socialpolitik, 2010)
In this paper, we present a new version of the OPTCON algorithm for the optimal control of nonlinear stochastic systems with special reference to econometric models. It delivers approximate numerical solutions of optimum control problems with a quadratic objective function for nonlinear econometric models with additive and multiplicative (parameter) uncertainties. The algorithm was programmed in C# and allows for deterministic and stochastic control, the latter with open-loop and passive learning (open-loop feedback) information patterns. We demonstrate the applicability of the algorithm by experiments with a small quarterly macroeconometric model for Slovenia. This shows the convergence and the practical usefulness of the algorithm and (in most cases) the superiority of open-loop feedback over open-loop controls.
Keywords: C61; B22; C88; 330; Optimal control; Stochastic control; Algorithms; Econometric modeling; Policy applications